Phloem cell responses to the feeding activity of Eriosoma lanigerum on Malus domestica - Nogueira, Ravena Malheiros; Bragança, Gracielle Pimenta Pereira; Picoli, Edgard Augusto de Toledo; de Oliveira, Denis Coelho; Isaias, Rosy Mary dos Santos (Frontiers in Plant Science, 2025)
IntroductionHemipteran gall vascular traits result from the access, piercing, and sucking of the inducer mouth parts directly in the xylem and phloem conductive cells. Herein, our focus relies on mapping the features of phloem cells in the proximal, median, and distal regions of Malus pumila stem galls and adjacent galled stems.MethodsPhloem cells were dissociated from gall fragments, the stem portions above and below the galls, and the proximal and distal regions of M. pumila stem galls. were measured. The comparison of the higher length and diameter of the sieve tube elements (STE) was evaluated considering the priority of nutrient flow to gall portions.ResultsIn the M. pumila - E. lanigerum system, there were no significant differences in the dimensions of the STE in the galls compared with those of the stem portions above and below the galls.DiscussionAt the cytological level, the callose deposited in gall STE and the decrease in the cell lumen area in the stem portion above the gall due to thickened nacreous cell walls have implications for nutrient flow. Peculiarly, the smaller sieve pores in the sieve plates of the STE located in the galls and stem portions above and below them and the deposition of P-protein in the stem portions below the galls limit the bidirectional transport of nutrients, benefiting the transport of photoassimilates to the gall proximal region and reducing the vigor of apple tree stems.